The Effect of Health Literacy on a Brief Intervention to Improve Advance Directive Completion: A Randomized Controlled Study - Paige C. Barker; Neal P. Holland; Oliver Shore; Robert L. Cook; Yang Zhang; Carrie D. Warring; Melanie G. Hagen (SAGE Publishing, 2021)
Objective Completion of an advance directive (AD) document is one component of advanced care planning. We evaluated a brief intervention to enhance AD completion and assess whether the intervention effect varied according to health literacy. Methods A randomized controlled study was conducted in 2 internal medicine clinics. Participants were over 50, without documented AD, no diagnosis of dementia, and spoke English. Participants were screened for health literacy utilizing REALM-SF. Participants were randomized in a 1:1 ratio to the intervention, a 15-minute scripted introduction (grade 7 reading level) to our institution's AD forms (grade 11 reading level) or to the control, in which subjects were handed blank AD forms without explanation. Both groups received reminder calls at 1, 3, and 5 months. The primary outcome was AD completion at 6 months. Results Five hundred twenty-nine subjects were enrolled; half were of limited and half were of adequate health literacy. The AD completion rate was 21.7% and was similar in the intervention vs. the control group (22.4% vs 22.2%, P  = .94).More participants with adequate health literacy completed an AD than those with limited health literacy (28.4% vs 16.2%, P  = .0008), although the effect of the intervention was no different within adequate or limited literacy groups. Conclusion A brief intervention had no impact on AD completion for subjects of adequate or limited health literacy. Practice Implications Our intervention was designed for easy implementation and to be accessible to patients of adequate or limited health literacy. This intervention was not more likely than the control (handing patients an AD form) to improve AD completion for patients of either limited or adequate health literacy. Future efforts and research to improve AD completion rates should focus on interventions that include: multiple inperson contacts with patients, contact with a trusted physician, documents at 5th grade reading level, and graphic/video decision aids. Trial Registration Number NCT02702284, Protocol ID IRB201500776